The Role of Cognitive Belief, Fusion and Distortion in Predicting the General Health of Couples - Hamidreza Samadifard; Mohammad Narimani (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: General health is composed of features that act as a shield in the face of stressful life situations and help couples have better performance in these situations. The present study was conducted to determine the role of cognitive belief, fusion and distortion in predicting the general health of couples. Materials and Methods: Research method was descriptive method. Population of the study included all couples in the city of Ardabil in 2016. 380 individuals (190 couples) were selected from parks and other public places through available sampling and using Krejcie and Morgan table. Data were analyzed using Pearson correlation coefficient and linear regression analysis. Results: The results showed a significant relationship between meta-cognitive beliefs (r=0.47, p<0.05), cognitive fusion (r=0.33, p<0.05) and cognitive distortion (r=0.28, p<0.05) with general health. Beta coefficients for predictor variables indicated metacognitive belief (β=0.34), cognitive fusion (β=0.28) and cognitive distortion (β =0.21) predict the general health of couples (p<0.05). Conclusion: It can be concluded that couples with higher levels of meta-cognitive beliefs, cognitive fusion and cognitive distortion enjoy lower general health.